Moving Home Gender, Place, and Travel Writing in the Early Black Atlantic - Gunning, Sandra (Duke University Press, 2021)
Sandra Gunning draws on nineteenth-century African diasporic travel writing to explore the conditions and possibilities of race, gender, sex, and class that early black Atlantic travel enabled.